Fenomena Embriologi dalam Al-Qur’an: Analisis Ayat-Ayat Penciptaan Manusia Perspektif Tafsir Ilmi - Maelina Putri Maratu Solihah; Fitriah Fitriah; Muhammad Dzikri Maulana; Maulana Hakim Al-Fazri; Andi Rosa (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to reveal the urgency of science in the perspective of the Qur'an, especially through the interpretation of Surah Al-Baqarah verse 164. This verse represents various natural phenomena and life processes that reflect the greatness and power of Allah, as well as being a source of reflection for intelligent humans. By using tafsir tahlili method and tafsir ilmi approach, this study emphasizes the integral relationship between revelation and science. The results of the study show that this verse encourages Muslims to observe, research, and take lessons from the signs of Allah's greatness in the universe, as well as being the basis for integration between faith and science. In conclusion, science is not only important in the development of human life, but also as a way to get closer to the Creator.